The Effect of Powtoon Learning Media on Fifth-Grade Students’ Ability to Identify Figurative Language - Khoirunnisa Khoirunnisa; Yamin Yamin (Journal of Educational Sciences, 2026)
The ability to identify figurative language is an important component of Indonesian language learning because it supports students’ language comprehension and literacy development. However, elementary school students often experience difficulties in understanding figurative language due to its abstract nature and limited use of engaging instructional media. This study aimed to examine the effect of Powtoon learning media on fifth-grade students’ ability to identify figurative language. A quantitative approach with a quasi-experimental method and pre-test post-test control group design was employed. The participants were 62 fifth-grade students at SDN Susukan 03 Pagi, East Jakarta, divided equally into experimental and control classes. Data were collected using multiple-choice tests and analyzed using descriptive statistics, normality and homogeneity tests, an independent samples t-test, N-Gain analysis, and effect size analysis. The results showed that the experimental class obtained a higher post-test mean score (85.16) than the control class (62.37), with a significant difference (p < 0.001). The experimental class also achieved a high N-Gain score (0.701). These findings indicate that Powtoon is effective in improving fifth-grade students’ ability to identify figurative language.